Environment‐Dependent Self‐Assembly of DNA Origami Lattices on Phase‐Separated Lipid Membranes. Issue 14 (16th May 2018) - Sato, Yusuke; Endo, Masayuki; Morita, Masamune; Takinoue, Masahiro; Sugiyama, Hiroshi; Murata, Satoshi; Nomura, Shin‐ichiro M.; Suzuki, Yuki
Abstract: Self‐assembly of designed nanostructures on a lipid membrane offers a powerful approach for enhancing the functionality of its surface. Here, the environment‐dependent assembly of blunt‐ended DNA origami structures on a phase‐separated lipid‐bilayer membrane consisting of liquid‐disordered (Ld) and solid‐ordered (So) phases is reported. Fluorescence microscopy and atomic force microscopy (AFM) imaging reveal that DNA origami structures preferentially bind to the So phase. At higher concentrations, blunt‐ended origamis form 2D lattices on the Ld phase through surface‐mediated self‐assembly. In contrast, those adsorbed on the So phase are less mobile and pack into aggregates. However, this situation is changed by adding NaCl. High‐speed AFM imaging reveals the mechanism underlying the NaCl‐induced changes, wherein the lattices on the Ld phase desorb from the surface while the packed aggregates on the So phase reorganize into the lattices. These results indicate that the formation of 2D lattices depends on the phase of the lipids; however, it can be tuned by ionic conditions, enabling us to select the domain on which the lattice is formed. The present results may guide the creation of membrane‐supported DNA nanostructures that self‐assemble into functional states in a lipid phase or ion‐responsive manner. Abstract : The lipid composition–dependent behavior of blunt‐ended DNA origami structures are investigated using fluorescence microscopy and atomic force microscopy. The DNA origamis on the liquid‐disordered (Ld) phase form 2D lattice arrays, whereas those on the solid‐ordered (So) phase are packed into aggregates. When surface mobility is varied by adding NaCl, the aggregates are transformed into 2D lattices.